Awareness, knowledge, and beliefs about Human Papillomavirus and its vaccine among Egyptian medical students: A cross-sectional national study - Muhammad Elmanzlawey; Mohamed Terra; Mohamed Baklola; Yara Ahmed; Mariam Abuelela; Ibrahim Noureddin Al-Kurd; Abdel-Hady El-Gilany (PLoS ONE, 2025)
Background Human papillomavirus (HPV) is a major cause of preventable cancers, including cervical, penile, and oropharyngeal cancers. Despite the availability of safe and effective vaccines, gaps in awareness, knowledge, and uptake persist globally, particularly in low- and middle-income countries. Medical students, as future healthcare providers, play a critical role in HPV prevention advocacy, making it important to understand their level of preparedness. Methods A cross-sectional analytical study was conducted during the 2024–2025 academic year among medical students enrolled in faculties of medicine across Egypt. Eligible participants included undergraduate and internship-year students who voluntarily completed an online questionnaire adapted from the validated Karki et al. instrument, assessing HPV awareness, knowledge, beliefs, and vaccine uptake. The tool was reviewed by a panel of public health experts and pilot-tested among 30 students. Data were analyzed using descriptive statistics, chi-square tests, Mann–Whitney U tests, and multivariable logistic regression. Results A total of 1,431 students participated; 91.0% were aware of HPV. Awareness was significantly associated with older age (p = 0.003), Egyptian nationality (p < 0.001), higher academic year (p < 0.001), urban residence (p = 0.002), and prior HPV-related education (p < 0.001). Knowledge of sexual transmission was high (97–98%), yet misconceptions persisted—67% believed HPV typically causes symptoms (p < 0.001), and 50% incorrectly identified HPV as herpesvirus (p = 0.004). Vaccine-related knowledge was limited: 78% believed the vaccine causes serious adverse effects (p < 0.001), and 70–76% thought it was intended only for sexually active individuals (p = 0.03). Logistic regression confirmed academic seniority (AOR = 2.41, 95% CI 1.85–3.12), urban residence (AOR = 1.74, 95% CI 1.28–2.36), and prior HPV education (AOR = 3.06, 95% CI 2.14–4.38) as strong independent predictors of awareness. Gender differences were also observed: males were more willing to vaccinate (44% vs. 36%, p = 0.02) but perceived lower personal risk (8% vs. 12%, p = 0.04), whereas females expressed greater safety concerns (22% vs. 15%, p = 0.03), higher perceived stigma (p = 0.01), and stronger recognition of HPV’s cancer threat (95% vs. 97%, p = 0.04). Conclusion While HPV awareness among Egyptian medical students is high, significant misconceptions about pathogenesis, prevention, and vaccine safety remain. Educational interventions, particularly those targeting early academic years, are essential to address these gaps, improve vaccine acceptance, and strengthen the role of future physicians in HPV prevention efforts.